ОТ СЎЗ ТУРКУМИГА ХОС СЎЗЛАРНИНГ МЕТАФОРИК ТАБИАТИ - Ҳамдамова, Х. (SCIENCE and SOCIETY, 2021)
The article describes the metaphorical nature, historical and etymological aspects, the lexical and semantic nature of the words used in the epic "Rustamkhan", and their relationship to epic heroes.
Keywords: epic; noun phrase; metaphor; epic hero; meaning; figurative meaning; genetic senema; bakhshi; text